STRATEGY FOR DEVELOPMENT OF MEDICAL CHECK UP UNIT SERVICES TO SUPPORT HEALTH SERVICES IN HOSPITALS - Devasmita, Devasmita; Tosepu, Ramadhan ((Jurnal Ilmiah Mahasiswa Kesehatan Masyarakat), 2024)
Background: Many people will always try to keep their body's health in top condition, but quite a few carry out medical check-ups (MCU) as a preventive measure by detecting disease as early as possible. This research aims to determine the strategy for developing medical check-up unit (MCU) services as a prevention effort by encouraging public interest in carrying out medical check-ups and optimizing hospital services. Method: Qualitative research methods are used to describe problem solving descriptively. The type and source of data used is secondary data sourced from previous research that is relevant to this research. The data that has been collected is then summarized and compiled in order to achieve problem solving and draw conclusions. Research Results/Discussion: The research results show that the strategy for developing medical check-up unit (MCU) services can be carried out using two strategies, namely market development and product development. Conclusion: One way to do market development is by forming a marketing unit whose task is to coordinate the marketing sector, from planning to monitoring the running of MCU unit services, as well as collaborating with companies that need health services. Product development can be done by making products that are more attractive to the market for the targets that have been set. In this case, MCU services in hospitals can take the form of flexible examination packages following trending health problems. Keywords: Medical Check-Up, Marketing Strategy, Health Services